Bright red circularly polarized luminescence of liquid crystalline polymer network films - Zonglin Li; Xuan Wang; Wei Zhang; Fengyun Shi; Hongkun Li (Next Materials, 2025)
Circularly polarized luminescence (CPL)-active functional materials have drawn extensive attention for their wide range of promising applications. However, the preparation of CPL materials with long-wavelength emission, large luminescence dissymmetry (glum) factors and high luminescence efficiency remains a challenging task. In this work, two liquid crystalline polymer network films were fabricated by photocrosslinking reactions of cholesteric liquid crystal mixtures containing an aggregation-induced emission luminogen. The resulting films exhibit bright red CPL with an absolute glum value up to 0.37 and a fluorescence quantum yield up to 73%. Furthermore, the films can be utilized for fabrication of patterns for anti-counterfeiting applications.